Male, female : the evolution of human sex differences - Geary, David C. (American Psychological Association, 2021)
"The questions of how and to what extent the sexes differ are long standing and controversial. In this authoritative classic, David C. Geary provides a comprehensive evaluation of these questions based on the principles of evolution, particularly sexual selection. Using an evolutionary framework, Geary describes how human sex differences are similar to those found in other species and how the expression of these differences is uniquely human. The principles of sexual selection such as female choice and male-male competition explain sex differences in parenting, mate choices, ways of competing for mates, social-political preferences, development, and brain and cognition. Far from being one-sided in the nature-versus-nurture debate, an evolutionary framework can easily incorporate the influence of experience and cultural context on the development and expression of sex differences. Thoroughly updated and expanded, this third edition includes a chapter on sex differences that emerge in modern contexts, such as differences in occupational choices and variation in sexual orientation, gender identity, and relationships. Scholars from a wide range of sciences have much to learn from this monumental volume"--